2022
DOI: 10.3390/nano12162776
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III)–Quercetin Complexes’ Safety for MRI Cell Tracking in Cell Therapy Applications: Cytotoxic and Genotoxic Assessment

Abstract: The theranostic agent iron–quercetin complex (IronQ) provides a T1-positive magnetic resonance imaging (MRI) contrast agent. The magnetically IronQ-labeled cells can be used for cell tracking and have active biological applications in promoting cell and tissue regeneration. However, a detailed investigation of IronQ’s cytotoxicity and genotoxicity is necessary. Thus, this study aimed to evaluate the possibility of IronQ inducing cytotoxicity and genotoxicity in peripheral blood mononuclear cells (PBMCs). We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…IronQ treatment was shown to slightly increase the production of reactive oxygen species (ROS) 18 , thus inducing oxidative stress and cellular activation. Our investigation demonstrated the upregulation of various stress-responsive and detoxifying genes, including MGST1, HPGDS, NQO1, PRDX1, TXN, TXNRD1, and EPX .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IronQ treatment was shown to slightly increase the production of reactive oxygen species (ROS) 18 , thus inducing oxidative stress and cellular activation. Our investigation demonstrated the upregulation of various stress-responsive and detoxifying genes, including MGST1, HPGDS, NQO1, PRDX1, TXN, TXNRD1, and EPX .…”
Section: Discussionmentioning
confidence: 99%
“…The paramagnetic IronQ has shown significant promise as a versatile theranostic agent, as it is both a contrast agent for magnetic resonance imaging and an invigorating therapeutic agent. This agent has demonstrated safety in cell tracking and therapy 18 . Given that our IronQ-PBMC-derived angiogenic cells originated from a readily accessible source and exhibited renewable tissue properties, as well as their cultivation using a versatile theranostic agent that was capable of stimulating PBMCs and enabling cell tracking via MRI, these cells hold tremendous promise for use in tissue repair strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published study by Yang et al ( 99 ) revealed that co-treatment of bone marrow mesenchymal stem cells (BMSCs) with Iron(III)-quercetin complexes (IronQ), which has excellent dual functions with the use of an imaging probe for MRI and act as a stimulating agent by favoring circulating proangiogenic cell differentiation ( 100 102 ), alleviates intracerebral hemorrhage (ICH) by ameliorating inflammation-induced neurological deficits through inhibition of the Mincle/Syk signaling pathway. The conditioned medium generated from BMSC combined with IronQ reduced the LPS-induced inflammation, Mincle expression and its downstream target activity in the BV2 cell line.…”
Section: Inhibition Of Mincle With Drugs Alleviates Inflammation-rela...mentioning
confidence: 99%
“…The main nanomaterials used for their fabrication are gold and silver, the oxides of iron, cooper, and the dioxides of titanium and silicon [ 160 ]. The QUE formulation into inorganic NPs is used either for imaging or for therapeutic purposes, especially in the cases of cancers, neurological, or metabolic diseases [ 161 , 162 , 163 , 164 ]. This review mainly focuses on the QUE delivery systems and includes the studies that propose inorganic nano-formulations assessed in-vitro or at preclinical levels in different disease conditions.…”
Section: Que Nanosystemsmentioning
confidence: 99%